Investigation of the effect of sunflower oil methyl esther on the performance of a diesel engine - Ilkiliç, C; Yücesu, HS (Taylor & Francis Inc, 2005)
The viscosity of raw vegetable oil is rather higher than that of diesel fuel. High viscosity has a negative effect on atomization quality, and so engine performance and exhaust emission are affected badly; this causes failure of engine parts. To decrease viscosity of vegetable oil, methyl ester was produced and tested as an alternative fuel in a single cylinder, four strokes, air-cooled diesel engine. The viscosity of sunflower oil methyl ester obtained after transesterification was reduced considerably and heating value was improved. Engine tests were carried out at full load-different speed range; the engine torque and power of sunflower oil methyl ester was lower than that of diesel fuel in range of 6 - 18% and specific fuel consumption was higher than that of diesel fuel of approximately 3%. CO2, CO and NOx emissions of sunflower methyl ester were lower than that of diesel fuel. The sunflower oil methyl ester fuel was used successfully as alternative fuel in short-term tests.
Keywords: alternative fuels; bio diesel; diesel fuel; sunflower oil methyl ester